Penerapan Model Discovery Learning dalam Mata Pelajaran SKI Untuk Meningkatkan Hasil Belajar Siswa MTsN 2 Aceh Besar - Azhar Azhar (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
The aim of this research is to see how the application of the discovery learning model in the Islamic Cultural History (SKI) subject has an impact on student learning outcomes in class VII MTsN 2 Aceh Besar. Classroom Action Research (CAR) with a double cycle design was used. There are 32 students in class VII-1 who have different levels of ability. Tests and observations are used to collect learning outcome data. The research results show that using discovery learning models in SKI subjects can improve student learning outcomes in class. After implementing these learning strategies, students show significant improvements in their conceptual understanding, their critical thinking skills, and their desire to learn. These results indicate that improving the SKI learning outcomes of class VII-1 MTsN 2 Aceh Besar students can be achieved through implementing a learning model that is different from the discovery learning model.